2004
DOI: 10.2337/diabetes.53.9.2353
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Intolerance in a Large Cohort of Mediterranean Women With Polycystic Ovary Syndrome

Abstract: The aim of this study was to investigate the phenotypic parameters and associated factors characterizing the development of glucose intolerance in polycystic ovary syndrome (PCOS). Among the 121 PCOS female subjects from the Mediterranean region, 15.7 and 2.5% displayed impaired glucose tolerance and type 2 diabetes, respectively. These subjects were included in a single group of overweight or obese subjects presenting with glucose intolerance (GI) states. PCOS women with normal glucose tolerance (81.8%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
86
5
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(111 citation statements)
references
References 54 publications
10
86
5
10
Order By: Relevance
“…In our cohort of 118 consecutive PCOS women with a mean age of approximately 29 years, 21% were diagnosed with either IGT or type 2 diabetes, according to the 2-h glucose concentration of an OGTT. This prevalence is similar to results reported for other PCOS cohorts of comparable age [15,16,41], and is significantly higher than the IGM prevalence in the general population [42]. Hence, screening of PCOS women for IGM has been recommended [13,17,19].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our cohort of 118 consecutive PCOS women with a mean age of approximately 29 years, 21% were diagnosed with either IGT or type 2 diabetes, according to the 2-h glucose concentration of an OGTT. This prevalence is similar to results reported for other PCOS cohorts of comparable age [15,16,41], and is significantly higher than the IGM prevalence in the general population [42]. Hence, screening of PCOS women for IGM has been recommended [13,17,19].…”
Section: Discussionsupporting
confidence: 84%
“…Women with PCOS often suffer from obesity, insulin resistance, IGT, or type 2 diabetes [14][15][16][17]41]. In our cohort of 118 consecutive PCOS women with a mean age of approximately 29 years, 21% were diagnosed with either IGT or type 2 diabetes, according to the 2-h glucose concentration of an OGTT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rancho Bernardo Study [11] studied 997 women aged 50 to 92 years and reported that earlier menarche was associated with higher fasting and post-challenge plasma glucose levels. In a study of 121 women with polycystic ovary syndrome, Gambineri et al [13] reported that earlier menarche onset was associated with impaired glucose tolerance. However, Cooper et al [12] found no association between age at Age at menarche (years)…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported associations between earlier age at menarche and higher blood glucose levels in adults, but they may have been underpowered to detect any association with diabetes risk [11][12][13]. We hypothesised that earlier age at menarche would also predict subsequent diabetes risk.…”
Section: Introductionmentioning
confidence: 93%